2020
DOI: 10.1021/acssuschemeng.0c05480
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Highly Efficient and Reversible Absorption of SO2 Using Ternary Functional Deep Eutectic Solvents

Abstract: The efficient and reversible capture of lowconcentration SO 2 in flue gas has attracted increasing attention. In this work, a series of novel ternary functional deep eutectic solvents (DESs) based on 1-butyl-3-methylimidazolium chloride (BmimCl) as a hydrogen bond acceptor and ethylene urea (EU) along with azole derivatives as hydrogen bond donors were prepared to investigate the low-concentration SO 2 absorption. Results demonstrated that the studied ternary DESs exhibited superior SO 2 capture performance at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…11 So far, various DESs have been examined for SO 2 capture, such as choline-based DESs, 12 betaine-based DESs, 13 imidazolium-based DESs, 14 and azole-based DESs. 11 a ,15 However, due to the disadvantages such as high viscosity and corruption caused by halogen anions, DESs are still lacking practical applications.…”
mentioning
confidence: 99%
“…11 So far, various DESs have been examined for SO 2 capture, such as choline-based DESs, 12 betaine-based DESs, 13 imidazolium-based DESs, 14 and azole-based DESs. 11 a ,15 However, due to the disadvantages such as high viscosity and corruption caused by halogen anions, DESs are still lacking practical applications.…”
mentioning
confidence: 99%
“…An interesting phenomenon accompanied by the absorption process is that the colorless solvent gradually turned to brown in CPL:Im DES (1:1), which was also observed by Liu et al [29]. Based on previous research, Tantai et al put forward a novel strategy to prepare ternary functionalized DESs capable of chemically binding ultralow concentration (2000 ppm) SO 2 in the flue gas, by mixing low-cost azole derivatives with ternary EU:BmimCl DESs [53]. By comparing the absorption capacity of ternary EU:4-CH 3 -Im:BmimCl DESs (1:1:1, 2:1:1, 1:2:1, and 1:1:2) with binary DESs, including EU:BmimCl DES (1:1), CH 3 -Im:BmimCl DES (1:1) and 4-CH 3 -Im:BmimCl DES (2:1), as shown in Table 2.…”
Section: Azole-based Functionalized Dessmentioning
confidence: 87%
“…For functionalized DESs, the stronger interaction between DESs and gases would make regeneration harder. For instance, due to the strong interaction between NO and DESs, the desorption rates of NO in Tetz:P 4444 Cl DES (1:1) [ [53]. Deng et al [49] reported that the different desorption behaviors of ACC:Im DES (1:2) and ACC:Tri DES (1:1) were related to the basicity of DESs.…”
Section: Regenerationmentioning
confidence: 99%
“…Fourier transform infrared (FT-IR) spectra were recorded using a Nicolet iN10 Fourier-transform spectrometer. 1 H and 13 C NMR spectra were performed on a Bruker 400M NMR spectrometer. The density was measured by a pycnometer.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Sulfur dioxide (SO 2 ), one of the chief pollutants in ambient air, is emitted largely from fossil fuel combustion and has caused environmental and health problems, such as acid rain, and damage of respiratory system. When healthy humans are repeatedly exposed to low concentrations of SO 2 , they may develop laryngitis, chronic bronchitis, and terrible infections of the respiratory tract . According to reports, the limits of human exposure to SO 2 gas in the long-term and short-term are 2 and 5 ppm, respectively.…”
Section: Introductionmentioning
confidence: 99%